2021
DOI: 10.3389/fpsyg.2021.741045
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Research Methods in Language Learning Psychology From a Complexity Dynamic System Theory Perspective

Abstract: Language learning is a dynamic and complex process in which different factors and variables are constantly interacting. However, many studies done on constructs related to teacher-learner psychology have used one-shot quantitative research designs, while it is impossible to capture the complexity and dynamism of such variables via one-time measurements. Against this gap, complexity dynamic system theory (CDST) has recently been applied to explore processes and changes that a construct may undergo. To shed more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…These findings are consistent with previous research that has shown the effectiveness of reflective practices on student reading comprehension achievement [88,89]. Moreover, it was clearly seen in this study that reflective teaching, which was to qualify method-centered teaching, had a larger effect size (Cohen's d) in comparison to the small to moderate effect sizes observed in other studies that reviewed reciprocal teaching, interactive teaching, and questioning techniques [23,29,34,35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with previous research that has shown the effectiveness of reflective practices on student reading comprehension achievement [88,89]. Moreover, it was clearly seen in this study that reflective teaching, which was to qualify method-centered teaching, had a larger effect size (Cohen's d) in comparison to the small to moderate effect sizes observed in other studies that reviewed reciprocal teaching, interactive teaching, and questioning techniques [23,29,34,35].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Bounouh and Merzoug's [22] study also pointed out that reciprocal teaching had significantly positive impacts on student reading comprehension achievement, with a moderate effect size (Cohen's d = 0.47). In a study of a systematic review about reciprocal teaching, the authors [23] concluded that reciprocal teaching is a promising approach supported by multiple learning theories and that it has consistently shown positive effects on reading comprehension outcomes. These reported studies showed the moderate effect size of reciprocal teaching on students' reading comprehension.…”
Section: Reciprocal Teachingmentioning
confidence: 99%
“…Studies utilising the CDST perspective differ from the typical quantitative and qualitative methods used to study teacher-learner psychology. There are unique CDST research properties: evolving and dynamically rephrasing research questions, a processoriented approach to understanding events considering one's cognition, emotion, social context, culture, and interaction, focus on individual experiences rather than generalisable patterns of behaviour, different analytical tools, and favouring opaque, longitudinal, and personal data instead of a large sample (Yang, 2021). CDST looks at the decline and disintegration of factors and processes as a whole.…”
Section: Complex Dynamic Systems Theory: a Paradigm Which Challenges ...mentioning
confidence: 99%
“…Complexity dynamic system theory is a theory that originated from hard sciences to study change, dynamism, and evolution of complex systems and subsystems of a phenomenon (Nematizadeh and Wood, 2019;Yang, 2021). It explores the underlying processes and factors involved in the performance of a variable and its related variables that dynamically interact to cause an event (Amerstorfer, 2020).…”
Section: Background Complexity Dynamic System Theorymentioning
confidence: 99%